Analysis of social dine-out preferences of the university members according to personal characteristics: a case study of the university in the Southwestern Region in the U.S. / Chang Lee. - Chang, Lee (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2010)
As the annual migration of new students to campuses occurs, college town populations are composed of younger generations from different regions with different characteristics. This study illustrates the way students, faculty, and staff view dining out attributes when they select a restaurant for social purposes. Attributes such as price, cuisine, atmosphere, service quality and food quality, name brand, location, convenience, architectural design, other customers, previous experience, and alcohol service are used to identify members’ social dining preferences. Furthermore, the study also observes whether the importance of dining attributes is different according to personal and dining out characteristics.